SBA‐15‐Oxynitrides as a Solid‐Base Catalyst: Effect of Nitridation Temperature on Catalytic Activity1. (20th March 2015) - Singh, Baljeet; Mote, Kaustubh R.; Gopinath, C. S.; Madhu, P. K.; Polshettiwar, Vivek
Abstract Solid bases, such as SBA‐15‐oxynitrides, have attracted considerable interest for potential applications as catalysts in important industrial processes. Reported herein is that by simply tuning the temperature of nitridation (ammonolysis), the catalytic activity of these solid bases can be enhanced. Solid‐state NMR spectroscopy and XPS studies provided the reasoning behind this change in activity.